Nanoplasmonic and Fluorescence Microscopy Studies of Cell Membrane Mimics - Johansson, Björn (My University, 2011)
Despite the fact that two thirds of all pharmaceuticals today target membrane proteins, we know rather little about them since the complexity of the cell membrane makes membrane proteins difficult to study. Furthermore, since membrane proteins control transport of molecules across cell membranes, it is also difficult to study such transportation processes. In this thesis a method for studying transport of molecules across artificial cell membranes, via simultaneous fluorescence microscopy and localized surface plasmon resonance sensing (LSPR), has been developed. The method utilize shear-driven lipid bilayer cell membrane mimics, where hydrodynamic forces in a micro fluidic channel introduced by bulk flow is used to move the bilayer. The bilayer is shear-driven over a nanostructured surface, producing a lipid bilayer spanning nanosized wells embedded in the surface. In the bottom of the wells are situated gold nanodisc nanoplasmonic sensing elements. The LSPR of the nanodiscs is sensitive to changes in the refractive index of the surrounding dielectric. The aim is that such a surface with embedded nanoplasmonic sensing elements in combination with a locally free spanning lipid bilayer will enable time resolved measurements of transport across the cell membrane mimic, into and out of the nanowells.
Keywords: Fysik; Physical Sciences